1998
DOI: 10.1093/jpepsy/23.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia Growth and Development Study: Relationships Between Neuropsychological, Neurological, and MRI Findings at Baseline

Abstract: Hemophilia-related morbidity has a subtle adverse influence on cognitive performance. HIV infection was not associated with neuropsychological dysfunction in this group even when MRI abnormalities were present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 17 publications
5
35
0
Order By: Relevance
“…Span percent correct and latency to correct were associated with the presence of a premorbid history of intracerebral hemorrhage, but were not sensitive to HIV status. This result parallels Sirois et al (1998), also reporting on the HGDS sample, who found that a documented history of head trauma was associated with lowered neuropsychological performance in both HIV1 and HIV2 groups. History of head trauma was relatively common in both HIV1 and HIV2 groups in both Sirois et al (1998) and the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Span percent correct and latency to correct were associated with the presence of a premorbid history of intracerebral hemorrhage, but were not sensitive to HIV status. This result parallels Sirois et al (1998), also reporting on the HGDS sample, who found that a documented history of head trauma was associated with lowered neuropsychological performance in both HIV1 and HIV2 groups. History of head trauma was relatively common in both HIV1 and HIV2 groups in both Sirois et al (1998) and the present study.…”
Section: Discussionsupporting
confidence: 88%
“…However, follow-up of HGDS participants over a period of 5 years revealed significant declines in neuropsychological performance that directly related to declines in immune functioning (Loveland et al, in press). Although neuropsychological deficits were not associated with HIV infection or immune suppression at baseline, lowered neuropsychological performance was found in HGDS participants with a history of head trauma and coordination and0or gait abnormalities that probably reflect hemophilia-related morbidity (Sirois et al, 1998). The results of both the Loveland et al (1994) and Sirois et al (1998) studies were interpreted as showing that adaptive behavioral, academic, and cognitive difficulties in the baseline HGDS sample reflect the effects of hemophilia as a chronic illness rather than the effects of HIV infection.…”
Section: The Hemophilia Growth and Development Studymentioning
confidence: 93%
“…Analyses of baseline and longitudinally collected HGDS data demonstrated associations between the functional severity of hemophilia, measured by abnormalities in coordination and gait, and academic performance. 11,12 Another HGDS report showed associations between prolonged hospitalization and lower achievement test scores in reading and spelling (Wong WY et al, unpublished data).…”
Section: Vs 413)mentioning
confidence: 99%
“…Analyses of baseline and longitudinally collected HGDS data demonstrated associations between the functional severity of hemophilia, measured by abnormalities in coordination and gait, and academic performance. 11,12 Another HGDS report showed associations between prolonged hospitalization and lower achievement test scores in reading and spelling (Wong WY et al, unpublished data).To extend observations made in the HGDS, the Academic Achievement in Children with Hemophilia study group was formed. Investigators from 18 comprehensive US hemophilia treatment centers collaborated in the collection of social, demographic, hemophilia-related, and psychological data from a population-based cohort of young school-aged children with severe hemophilia in an effort to further define relationships between hemophilia and academic performance.…”
mentioning
confidence: 99%
“…1,27,29 -33 However, Cohen et al 34 did not find significant differences between HIV-infected and noninfected children in global intellectual ability, even 4 1 ⁄2 to 8 1 ⁄2 years after onset, and others [35][36][37] have noted that neuropsychological profiles in HIV-infected and noninfected hemophiliacs did not differ. Thus, infants and children infected with HIV infection have, sometimes, but not always, been found to have deficits in global intellectual functioning.…”
mentioning
confidence: 95%